1995
DOI: 10.1104/pp.109.2.375
|View full text |Cite
|
Sign up to set email alerts
|

The Biochemical Response of Electrical Signaling in the Reproductive System of Hibiscus Plants

Abstract: Stimulation of the stigma of Hibiscus flowers by pollen, wounding (heat), or cold shock (4°C) evokes electrical potential changes in the style, which propagate toward the ovary with a speed of 1.3 to 3.5 cm s-'. Potential changes were measured intracellularly by microelectrodes inserted i n the style. l h e resting potential ranged from -90 to -112 mV (n = 20) in cells of the vascular tissue and from -1 84 to -220 mV (n = 22) in cells of the pollen-transmitting tissue.The amplitude of the potential changes was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 22 publications
1
45
0
Order By: Relevance
“…Electric fields induce responses in insects [7,8,28]. A biologically relevant property of body surface charge in pollinating insects was traced to the opposite polarity of their body surface charge to that of flowers, potentially facilitating pollen collection and possibly leaving a cue after electrical neutralization of the flowers' electric field [9][10][11][12]. It has also be noted that charged pollen powder sprayed over flowers leads to fertilization of these flowers [29], and biopesticides may be more effective if electrically charged [30].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Electric fields induce responses in insects [7,8,28]. A biologically relevant property of body surface charge in pollinating insects was traced to the opposite polarity of their body surface charge to that of flowers, potentially facilitating pollen collection and possibly leaving a cue after electrical neutralization of the flowers' electric field [9][10][11][12]. It has also be noted that charged pollen powder sprayed over flowers leads to fertilization of these flowers [29], and biopesticides may be more effective if electrically charged [30].…”
Section: Resultsmentioning
confidence: 99%
“…Naturally occurring surface charge is thought to play a role in pollination [9][10][11] reviewed by [12], since flowers were found to be usually negatively charged, whereas the arriving insects appear to carry a positive surface charge. The electric charge that accumulates on the cuticle of flying insects discharges only partially upon landing because of the high contact resistance between legs and ground.…”
Section: Introductionmentioning
confidence: 99%
“…Vian et al (1999) induced rapid and systemic accumulation of chloroplast mRNA-binding protein transcripts, in tomato (Lycopersicon esculentum), after flame stimulus. In addition to translation and transcription, evidence exists for a role of electrical signals in many processes of plant life, including respiration (Dziubinska et al, 1989;Filek and Koscielniak, 1997), water uptake (Davies et al, 1991), phloem unloading (Fromm, 1991), and phloem translocation (Fromm and Bauer, 1994) as well as fertilization (Fromm et al, 1995). Recently, this account was extended by a study on the inhibition of photosynthesis in Mimosa pudica (Koziolek et al, 2004) upon flame wounding, which demonstrated that electrical signals triggered transient changes in chlorophyll fluorescence (PSII electron quantum yield) and leaf gas exchange.…”
mentioning
confidence: 99%
“…Electrical potentials generated after depositing an improper pollen on the stigma differed from those induced by a proper pollen. Similar preparation of the ovary for acceptance of the male cell was demonstrated in Hibiscus (Fromm et al 1995). Stimulation of the plant stigma with a compatible pollen induced series of APs, which are propagated along the style to the ovary.…”
Section: Physiological Role Of Electrical Activity In Plantsmentioning
confidence: 92%